2017
DOI: 10.1093/brain/awx233
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal intrinsic brain functional network dynamics in Parkinson’s disease

Abstract: for a scientific commentary on this article. Parkinson's disease is a neurodegenerative disorder characterized by nigrostriatal dopamine depletion. Previous studies measuring spontaneous brain activity using resting state functional magnetic resonance imaging have reported abnormal changes in broadly distributed whole-brain networks. Although resting state functional connectivity, estimating temporal correlations between brain regions, is measured with the assumption that intrinsic fluctuations throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
359
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(410 citation statements)
references
References 85 publications
43
359
8
Order By: Relevance
“…Conversely, WM functional networks become more optimal in PD patients. This was different from previous findings concerning WM structure (Galantucci et al, 2017) and GM function (Gottlich et al, 2013;Kim et al, 2017) in PD patients, and suggests a functionalstructural decoupling at the network level.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, WM functional networks become more optimal in PD patients. This was different from previous findings concerning WM structure (Galantucci et al, 2017) and GM function (Gottlich et al, 2013;Kim et al, 2017) in PD patients, and suggests a functionalstructural decoupling at the network level.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our results, Peraza et al (2015) reported no difference between AD and controls with respect to global efficiency which indicates that static and dynamic changes in efficiency might be a specific feature of DLB that might not be associated with dementia per se. In contrast to our results, Kim et al (2017) found increased variability of global efficiency in PD. However, this finding was not replicated in another study in PD patients with mild cognitive impairment and thus further research will be needed to identify the specific changes related to these different Lewy body diseases.…”
Section: Dlb-related Changes In Dynamic Network Topologycontrasting
confidence: 99%
“…Just one previous static connectomic study has found that MDD with SI reduced functional connectivity in the orbitofrontal‐thalamic network (Kim et al, b). In addition, the nodal properties (i.e., nodal strengths, nodal clustering coefficients, and nodal efficiency) of the left orbital part of the superior frontal and the bilateral thalamus gyrus were significantly correlated with SSI scores (Kim et al, b). Consistent with previous findings on static connectomic, we found that the putamen, temporal, and frontal cortices showed group differences.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, resting‐state (absence of the stimulus) functional magnetic resonance imaging (fMRI) studies have reported that depressed patients with SI exhibited disrupted functional connectivity between the rostral anterior cingulate cortex and orbitomedial prefrontal cortex, that is, brain regions associated with decision‐making and emotional processing in SI (Du et al, ). In addition to the aforementioned seed‐based analysis of functional connectivity, recent functional connectomic study suggested that MDD with SI is characterized by decreased functional connectivity in the orbitofrontal‐thalamic circuits (Kim et al, b). Moreover, an anatomical connectomic study suggested that MDD with SI was associated with a reduction of the anatomical connectivity in frontal–subcortical circuits (Myung et al, ).…”
Section: Introductionmentioning
confidence: 99%